REPRESENTASI PENAFSIRAN KLASIK DALAM TAFSIR DIGITAL: Analisis Wacana pada Tafsirweb.com - Azka Zahro Nafiza; Sutrisno Hadi (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2025)
Digital transformation in Islamic Studies, particularly in Qur’anic Exegesis, has created new opportunities and expanded accessibility to knowledge. However, this development raises profound questions regarding the representation of Islamic intellectual heritage in digital spaces. This study examines the representation of classical exegesis on the Indonesian digital platform, tafsirweb.com. It operates on the premise that digitisation of tafsir is not a passive process, but rather involves active construction, filtering, and presentation that can shape users’ understanding of classical interpretive narratives. Employing library research and a qualitative-analytical approach, this study applies Norman Fairclough’s Critical Discourse Analysis as its theoretical framework. The findings indicate that although tafsirweb.com appears neutral, it actively constructs the authority of classical exegetes through metadata and the prioritisation of specific commentaries. The use of literal and hierarchical diction fosters a restrictive understanding, while the assumption of the Qur’anic Arabic’s transparency without further contextualization further reinforces this authority. The platform’s content curation practices and fragmented discourse consumption patterns tend to reflect Sunni mainstream perspectives, potentially leading to decontextualization and erosion of traditional authority. Socio-culturally, the platform functions as a counter-narrative while simultaneously reinforcing an epistemic-conservative ideology on one hand, safeguarding Islamic doctrine, yet on the other hand, potentially inhibiting contextual interpretation.